Determination of lead in wax crayon using flame atomic absorption spectrometry / Suhailey binti Mohd Noor - Mohd Noor, Suhailey (2014)
The method for the determination of lead in wax crayon by Flame Atomic Absorption Spectrometry was adopted from Health Canada Safety Program (HCSP), Product Safety Laboratory, ‘Determination of Total Lead in Wax Crayon by Closed Vessel Micowave Digestion’ and verified. The parameter of method verification such as accuracy, precision, limit of detection, limit of quantitation and linearity were studied. Three colours from 10 boxes of wax crayon samples were analysed. Microwave digestion method was used to extract the lead prior to analysis. The concentration of lead in red, blue and orange colour wax crayon was 25.23 ± 3.26 mg kg-1, 21.21 ± 3.44 mg kg-1 and 32.15 ± 0.35 mg kg-1 respectively. Our results also indicate that, there is no significant different in lead content between blue and red colour wax crayon. However, there is significant different in amount of lead in orange colour compared to blue and red colour wax crayon. Previous study had estimated that a greater than 15 ug/day intake of available lead could cause a previously normal child to exceed a 10 ug/dl blood level which gave toxic effect to children.